Psychological well- being and its relationship to academic achievement at Sultan Qaboos University - Sultanate of Oman - Al-Abri, Hilal Salem Suleiman (Journal of Educational and Psychological Sciences, 2023)
This study aimed to measure the psychological well- being of the students of Sultan Qaboos University, Sultanate of Oman, as well as the level of academic achievement of the students. The researcher chose a random sample from the university student community for the academic year 2020/2021, which included 485 male and female students distributed among the university’s various faculties, 295 female students and 195 male students.The Raive Psychological Well- Being Scale was applied, as the arbitrators' validity and reliability were verified by Cronbach's alpha method. The study concluded that Sultan Qaboos University students enjoy a high degree of psychological well- being, with a percentage of (77%) of the sample tending to females. The study also concluded that there were no statistically significant differences between the sexes due to the college variable.With regard to academic achievement, the study concluded that (28%) of university students enjoy a GPA between 3.01- 3.9 (very good) who tend to have more female students. Regarding the relationship between psychological well- being and academic achievement, the study concluded that there is a weak direct relationship between the two variables.The study came out with a set of recommendations, the most important of which are legalizing the satisfaction of students’ desires in acquiring various means of entertainment so that they can be used as an incentive for academic achievement and achievement, designing programs that correspond to the varying academic achievement of students in line with different levels of psychological well- being, and activating the role of counseling and psychological guidance for students who obtain low grades. In psychological well- being, preparing and codifying a measure of psychological well- being that is compatible with the university community and is commensurate with the nature of the Omani society.
Keywords: Psychological well- being; Academic achievement